The optimization of peritoneal dialysis training in long-term - Gursu, Meltem; Shehaj, Larisa; Elcioglu, Omer Celal; Kazancioglu, Rumeyza (Frontiers in Nephrology, 2023)
Peritoneal dialysis is a home based therapy for patients with advanced chronic kidney disease. This method provides adequate clearance of uremic toxins and removal of excess fluid when a proper dialysis prescription is combined with patient adherence. Peritonitis is the most frequent infectious complication among these patients and may render the continuity of the treatment. Training patients and their caregivers have prime importance to provide proper treatment and prevent complications including infectious ones. The training methods before the onset of treatment are relatively well established. However, patients may break the rules in the long term and tend to take shortcuts. So, retraining may be necessary during follow-up. There are no established guidelines to guide the retraining of PD patients yet. This review tends to summarize data in the literature about retraining programs and also proposes a structured program for this purpose.